Digital modeling of geomorpho-tectonic indicators in Valley Al-Ratka basin using remote sensing and geographic information systems - Shehab, Awrad; Fayyad, Ahmed (Al-Adab Journal, 2024)
Through the application of geomorpho-tectonic indicators, which are closely related to the shape of the river network and its measurements, it was found that the region has a high and medium tectonic index, meaning that the region suffers from tectonic changes that have a sudden impact on the landforms, and it also shows the relationships between the building processes with their corresponding forms. The earth’s surface. It is worth noting that geomatics technologies have achieved application on data within its inputs (DEM - Raster Image Satellite), and within digital analysis software and building a geographical database, which reflects the possibility of planning for environmental sustainability in the region, The indicators differ from one place to another within its geographical location. The study dealt with a quantitative analysis of the secondary basins of the study area using equations of geomorphological indicators of the valleys, which indicate or indicate the presence of tectonic activity As the river network was extracted through the Digital Elevation Model (DEM) and the region was divided into (6) secondary basins, and then the equations of geomorphological indicators were applied, the collection of these indicators, and the design of a model showing the degrees of tectonic activity for each basin in the region. The study concluded that the region has high and medium tectonic activity.